Individual tree traits shape insect and disease damage on oak in a climate‐matching tree diversity experiment. Issue 15 (17th July 2019) - Field, Elsa; Schönrogge, Karsten; Barsoum, Nadia; Hector, Andrew; Gibbs, Melanie
Abstract: Diversifying planted forests by increasing genetic and species diversity is often promoted as a method to improve forest resilience to climate change and reduce pest and pathogen damage. In this study, we used a young tree diversity experiment replicated at two sites in the UK to study the impacts of tree diversity and tree provenance (geographic origin) on the oak ( Quercus robur ) insect herbivore community and a specialist biotrophic pathogen, oak powdery mildew. Local UK, French, and Italian provenances were planted in monocultures, provenance mixtures, and species mixes, allowing us to test whether: (a) local and nonlocal provenances differ in their insect herbivore and pathogen communities, and (b) admixing trees leads to associational effects on insect herbivore and pathogen damage. Tree diversity had variable impacts on foliar organisms across sites and years, suggesting that diversity effects can be highly dependent on environmental context. Provenance identity impacted upon both herbivores and powdery mildew, but we did not find consistent support for the local adaptation hypothesis for any group of organisms studied. Independent of provenance, we found tree vigor traits (shoot length, tree height) and tree apparency (the height of focal trees relative to their surroundings) were consistent positive predictors of powdery mildew and insect herbivory. Synthesis . Our results have implications for understanding the complex interplay between tree identity and diversity in determining pest damage, and show that tree traits, partially influenced by tree genotype, can be important drivers of tree pest and pathogen loads. Abstract : We found that the effects of both tree species and genetic diversity were variable, suggesting that forest diversity effects on pests and pathogens can be unpredictable across space and time. In addition, we show that individual tree vigour and growth relative to surrounding trees can drive colonisation of tree hosts by herbivores and pathogens, providing compelling support for both the plant vigor and plant apparency hypotheses.